Home boy : a novel - Naqvi, H. M. (New York : Shaye Areheart Books, 2009)
Three young Pakistani men in New York City at the turn of the millennium have the guts to claim the place as their own. But when they embark on a road trip to the hinterland weeks after 9/11 in search of the Shaman, a Gatsbyesque compatriot who seemingly disappears into thin air, things go horribly wrong. Suddenly, they find themselves in a changed, charged America.
Keywords: September 11 Terrorist Attacks, 2001 -- Fiction; Pakistani Americans -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction